O Programa Bolsa Família e os seusiImpactos na redução do abandono escolar no Ensino Médio no Município de Acaraú-CE, no período 2018-2019 - Araújo, Terezinha Célia de Sousa (2019)
The research presents a study about the Bolsa Família Program and its impacts in the reduction of the dropout in the high school in the municipality of Acaraú-CE, in the period between 2018-2019. It aimed to analyze the relevance of the Bolsa Família Program (BFP), and more specifically, its impacts on reducing the dropout of the poorest and most vulnerable social groups in the municipality of Acaraú-CE, enrolled in high school. The methodology of this research was developed from a perspective of evaluation of social public policy, in depth and counter-hegemonic. The approach was qualitative, based on quantitative data and used as procedures: bibliographic review based on authors, Laws, Decrees and Legal Documents. In the context of the six high schools in the municipality of Acaraú, 23 BFP beneficiary parents and school managers were interviewed and a questionnaire was applied to a sample of 556 BFP beneficiary students. Also interviewed in the respective municipality, the Secretary of Social Assistance, the Municipal Manager of CadÚnico and BBP, and the interviewer of the BFP as well. It is noteworthy that, in addition to the interviews and the application of the questionnaire, observations permeated all moments of the study. In the final considerations, the analysis refers to the BFP as a federal public policy of a social nature, created in the Lula Government (2003-2010), to address poverty and misery in Brazil, and it is extremely important for the poor and extremely poor families of Acaraú, in terms of "help" in education, health, self-esteem and autonomy of women, in school attendance, and it is also an important ally in the confrontation and minimization of dropout in high school. It has been configured as one of the factors that has been driving the economy of the municipality, it has allowed the granting of credit to its beneficiaries, it is providing them positive changes in family life, even though the data show that most of them remain conditioned to the situation of poverty.